Driver Behaviour at Signalized Intersection Literature Review - Li Idi'il Fitri; Nasution, Harmein; Nurul huda, Listiani (TALENTA Publisher, 2023)
Traffic accidents are one of the highest causes of death in the world, with human behavior being the most dominant factor. Therefore, it is necessary to understand driver behavior as a traffic accident mitigation strategy. This paper aims to understand the behavior of drivers at signaled intersections and to overcome the deviant behavior. The behavior of the driver at the intersection is to stop or cross the intersection. Crossing at an intersection at a red light is deviant behavior. This deviation can occur as violation due to driver aggression or error due to a dilemma when the light is yellow. The influencing factors are personal, speed, acceleration, distance, the presence of other vehicles, and others. The main countermeasure for deviant behavior at intersections is law enforcement, such as the installation of red light cameras. In addition, the behavior of drivers at intersections can be used as a reference in the design of safer intersections.